Research on the Impact of Lighting Illuminance and Color on Creative Performance and Mood - Bo Zhou; Yangxiaoxiao Zhou; Qixuan Ren; Li Peng; Yang Guan; Haiyin He (Buildings)
With the development of the knowledge economy, the significance of the creative industry has become increasingly prominent. Individual creativity can be stimulated by optimal lighting. This research consists of two parts: Part I examines the effects of illuminance and color temperature on creativity through three experiments, while Part II employs a two-factor repeated-measures design to investigate their interaction effects. The participants completed creativity tests during light exposure, including TTCT tasks in Part I of the experiment, and AUT and RAT tasks in Part II. They also completed questionnaires to assess their mood, and HRV data were collected for physiological analysis. The results showed that the subjects performed worse on a creativity test at an extremely low illuminance of 150 lx. Within a comfortable neutral lighting range, the participants’ creativity at 300 lx was superior to that at 1500 lx. In exploring light color, the conventional correlated color temperature (CCT) variable was replaced with colored lighting. The results indicated that both blue and orange light enhanced creative performance compared to white light. Additionally, an interactive effect of illuminance and colored lighting was observed. Fluency on the Alternative Uses Task (AUT) test was greater under 5000 K and 300 lx lighting, while originality on the AUT test was enhanced under 1500 lx, colored lighting. Emotional experience was found to be significantly correlated with creative performance. These findings contribute to the development of a design guideline that utilizes lighting intensity, color, and other elements to foster a relaxing indoor atmosphere that enhances positive mood and creativity.